2018
DOI: 10.1021/acs.est.8b02320
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Remediation and Methane Emission Manipulation Using Surface Oxygen Nanobubbles

Abstract: Algal blooms in eutrophic waters often induce anoxia/hypoxia and enhance methane (CH) emissions to the atmosphere, which may contribute to global warming. At present, there are very few strategies available to combat this problem. In this study, surface oxygen nanobubbles were tested as a novel approach for anoxia/hypoxia remediation and CH emission control. Incubation column experiments were conducted using sediment and water samples taken from Lake Taihu, China. The results indicated that algae-induced anoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 46 publications
4
43
0
Order By: Relevance
“…The oxygen-locking layer could affect many geochemical and microbial processes, thereby opening a new possibility to remediate sediment, especially for deep waters, which are usually very difficult. For instance, oxygen nanobubble-MLS can be used to remediate the sediment to reduce methane emissions [26]. Another effective way to lock phosphorus in the sediment is to use Phoslock, which has so far been tested in about 200 water bodies worldwide [31].…”
Section: Deep Watersmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxygen-locking layer could affect many geochemical and microbial processes, thereby opening a new possibility to remediate sediment, especially for deep waters, which are usually very difficult. For instance, oxygen nanobubble-MLS can be used to remediate the sediment to reduce methane emissions [26]. Another effective way to lock phosphorus in the sediment is to use Phoslock, which has so far been tested in about 200 water bodies worldwide [31].…”
Section: Deep Watersmentioning
confidence: 99%
“…This oxidized capping layer can prevent the consumption of dissolved oxygen in the water column by the anaerobic substances from the sediment underneath the capping layer [24,25]. Furthermore, it has been demonstrated that emissions of the greenhouse gases CH 4 and CO 2 from eutrophic waters can be substantially reduced through the oxygen nanobubble-MLS treatment [26]. Thus, the oxygen nanobubble-MLS treatment may provide a principle for delivering oxygen down into deep waters or sediment without the need for mixing energy (e.g., pumps) to combat anoxia/hypoxia problems that are crucial for eutrophication control [27].…”
Section: Introductionmentioning
confidence: 99%
“…257 Another threat of algae-induced anoxia/hypoxia in the environment is through the emission of greenhouse gases, especially methane. 258 Studies indicate that algae-induced anoxia/hypoxia could be reduced or reversed after oxygen nanobubble loaded zeolite was added to anoxic sediment and methane emission was reduced by 3.2 times compared to the control. 258 Nanoclays or zeolites carrying nanobubbles are particularly useful because this technique offers a controlled and continuous supply of oxygen to the affected environment over a sustainable time period.…”
Section: Metal and Metal Oxide Nano-particles (Nps)-nanoclay Compositesmentioning
confidence: 99%
“…258 Studies indicate that algae-induced anoxia/hypoxia could be reduced or reversed after oxygen nanobubble loaded zeolite was added to anoxic sediment and methane emission was reduced by 3.2 times compared to the control. 258 Nanoclays or zeolites carrying nanobubbles are particularly useful because this technique offers a controlled and continuous supply of oxygen to the affected environment over a sustainable time period. Zhang et al 256 reported that the application of nanobubble@clay particles on lake sediment (B2 cm height with 100 g material) could increase dissolved oxygen in the sediment-water interface from 4 mg L À1 to 6 mg L À1 , which was sustained for B127 days.…”
Section: Metal and Metal Oxide Nano-particles (Nps)-nanoclay Compositesmentioning
confidence: 99%
“…Interfacial oxygen nanobubbles can be loaded on natural zeolites (specific gravity of 2.15-2.25 g cm −3 ), which are persistent clay minerals and unlikely to add extra ecological pressure to aquatic ecosystems (Lyu et al, 2019). Moreover, oxygen nanobubbleloaded zeolites can settle naturally to the designated areas like surface sediment, at which they can release oxygen to remediate hypoxia/anoxia (Shi et al, 2018). As Hg methylation tends to occur in the anaerobic conditions, the mitigation of hypoxia/anoxia by O2 nanobubbles might induce a reduction in the MPA of surface sediment.…”
Section: Introductionmentioning
confidence: 99%